THE BUTTERFLY EFFECT PERANG ANGLO-SATSUMA SEBAGAI AWAL MODERNISASI DI JEPANG - Ramadhani, Devita Rizqi Haning; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This study analyzes how modernization in Japan occurred due to the influence of Japan's defeat when the Satsuma troops faced British in the Anglo – Satsuma War which was triggered by the death of a British Shanghainese merchant in Namamugi. Japan is aware of their country's differences in strength in terms of military and technology, to improve both of these things the Satsuma people continue a modernization project called the Shuseikan Project with the main founder of this project a daimyo from the 28th Satsuma clan, this project continued with a new mission after sent several students from Satsuma to study in England and bring new knowledge upon their return to Satsuma. This study uses a qualitative method, with data collection techniques through literature study sourced from several books, journals, articles, websites. This study uses the perspective of Liberalism and Modernization theory. The results of this paper show that Japan is the first country in Asia to have succeeded in imitating the industrial revolution by absorbing knowledge from the West and increasing military strength and new technologies thanks to the Shuseikan project in Satsuma. This success can be seen as a butterfly effect from the Namamugi incident which escalated into a major war between Japan and Britain so that Japan realized the difference in strength and the importance of modernizing. Keywords: Anglo – Satsuma War, Butterfly Effect, Satsuma.